Addition of nimotuzumab to concurrent chemoradiotherapy after induction chemotherapy improves outcomes of patients with locally advanced nasopharyngeal carcinoma - Run-Jie Wang; Rui-Quan Ke; Yi-Feng Yu; Guan-Zhong Lu; San-Gang Wu (Frontiers Media S.A., 2024)
Purpose:To investigate the survival outcomes and toxicities associated with the addition of nimotuzumab to concurrent chemoradiotherapy (CCRT) in locally advanced nasopharyngeal carcinoma (LANPC) patients who received induction chemotherapy (IC).Methods:Patients with stage III-IVA nasopharyngeal carcinoma who received IC and CCRT between January 2017 and October 2021 were retrospectively included. We aimed to compare the locoregional recurrence-free survival (LRFS), distant metastasis-free survival (DMFS), disease-free survival (DFS), and overall survival (OS) between patients treated with CCRT+nimotuzumab and CCRT alone.Results:We included 411 patients in the analysis. Of these patients, 267 (65.0%) and 144 (35.0%) had CCRT+nimotuzumab and CCRT alone, respectively. Similar LRFS was found between those with and without nimotuzumab (92.9% vs. 92.6%, p = 0.855). The 3-year DMFS was 88.2% and 76.2% in those with and without nimotuzumab (p = 0.002). The 3-year DFS was 83.4% and 70.6% in those with and without nimotuzumab treatment (p = 0.003). The 3-year OS was 92.1% and 81.1% in those with and without nimotuzumab (p = 0.003). The multivariate Cox regression analysis indicated that the addition of nimotuzumab was independently associated with better DMFS (hazard ratio [HR] 0.606, p = 0.049), DFS (HR 0.613, p = 0.028), and OS (HR 0.497, p = 0.019). No significant differences in major toxicities were found between the two treatment arms, including hematologic toxicities, hepatoxicity, nephrotoxicity, gastrointestinal reactions, and mucositis (all p > 0.05).Conclusion:The addition of nimotuzumab to CCRT after IC in LANPC has shown promising results in improving treatment outcomes and acceptable toxicities.